2020
DOI: 10.1175/jhm-d-19-0209.1
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Inference Model Based on Random Forests to Identify the Effect of Soil Moisture on Precipitation

Abstract: Soil moisture influences precipitation mainly through its impact on land-atmosphere interactions. Understanding and correctly modeling soil moisture-precipitation (SM-P) coupling is crucial for improving weather forecasting and subseasonal to seasonal climate predictions, especially when predicting the persistence and magnitude of drought. However, the sign and spatial structure of SM-P feedback are still being debated in the climate research community, mainly due to the difficulty in establishing causal relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…The high performance variability of merged products across space (Fig. S5) is consistent with previous studies (Beck et al, 2021;Karthikeyan et al, 2017;Li et al, 2020b;Wang et al, 2021a;Yuan and Quiring, 2017). The high RM-SEs of the merged products in the shallower soil layers across the water bodies and evergreen needleleaf forests (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The high performance variability of merged products across space (Fig. S5) is consistent with previous studies (Beck et al, 2021;Karthikeyan et al, 2017;Li et al, 2020b;Wang et al, 2021a;Yuan and Quiring, 2017). The high RM-SEs of the merged products in the shallower soil layers across the water bodies and evergreen needleleaf forests (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The ranges of performance metrics of the new datasets against in situ data (Figs. 2 and S5) were broadly within the estimates reported by previous SM evaluations, although making a strict comparison is difficult because of the widely different spatiotemporal coverages and resolutions (Beck et al, 2021;Karthikeyan et al, 2017;Li et al, 2020b;Wang et al, 2021a;Yuan and Quiring, 2017). These results demonstrated that the merging procedures (unweighted averaging, OLC, EC) used were effective in creating relatively accurate long-term multilayer SM data at the global scale.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Li, Shangguan, et al. (2020) had shown that the topographic factors highlighted the SM–P interactions in the southwestern United States. By comparison, at all frequencies, GCCs were significantly correlated with meteorological factors in Nebraska, while soil texture was more important in determining GCCs in Utah.…”
Section: Resultsmentioning
confidence: 99%
“…To address the above questions, two regions with different climatic conditions (e.g., from semiarid and subhumid climates in Nebraska to arid and semiarid climates in Utah; T. Wang et al., 2017a) were selected from the continental United States, which have been hotspots for studying SM–P interactions (L. Chen & Dirmeyer, 2017; Ford, Rapp, et al., 2015; Koster et al., 2004; Li, Shangguan, et al., 2020). Observed long‐term SM and P data were obtained from regional monitoring networks in both regions, namely the Nebraska Mesonet (NM) for Nebraska and part of the Soil Climate Analysis Network (SCAN) for Utah.…”
Section: Introductionmentioning
confidence: 99%